Preservation of Traditional Game Values as Educational Tourism Assets in Sindangkerta District, Indonesia - DAMAYANI, Ninis Agustini; SAEPUDIN, Encang; BUDIONO, Agung; RACHMAWATI, Tine Silvana (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
Traditional games (Sundanese) as part of a culture potentially become educational tourism assets. This is based on two things, namely the values contained in the game and how to play. The values presented in this game can build children's character, namely honesty, leadership, cooperation, caring for the environment, loving cleanliness, and being aware. While in terms of playing traditional games can be classified into play (recreation), games to compete (competitive), and games that are educational. Thus through traditional children's games it is not only entertaining but also learning and competing. Based on this, this study aims to determine the preservation of the values of traditional games as educational tourism assets in the Sindangkerta area, Cipatujah District, Tasikmalaya Regency. The research method used is qualitative. The selection of this method with the consideration that the nature of the research data is able to maintain the integrity of the object. This means that data relating to research is understood as an integrated unit. The process of collecting data through interviews, discussions, observations, and library studies. Validity and reliability tests are carried out through the process of data triangulation and source triangulation. Descriptive data analysis through stages of data reduction, data presentation, and conclusion drawing. The sources of data in this study are taken from 3 people with details, 1 community leader and 2 managers of Saung Budaya Tatar Karang. The results of the study showed that the preservation model of traditional game values developed in Sindangkerta area was based on the Culture Experience and The Culture Knowledge with the principle of life “silih asih, silih asah dan silih asuh”. Preservation through Culture Experience through the implementation of regular games with a variety of games and Culture Knowledge through documenting various traditional games. Documentation results were made into community library collections. Through this preservation process traditional games are potential tourism assets that can be developed into educational tourist destinations. Through the introduction of traditional games, tourists will be treated to and included in a game. By participating in this game, tourists are expected to be able to absorb the character values contained in it. From the results of the study it can be concluded that the preservation model of traditional game values has been able to build public awareness in preserving Sundanese culture, especially traditional games.